Peran tradisi Gantangan dalam pelestarian nilai-nilai budaya lokal di Kabupaten Subang: The role of the Gantangan tradition in preserving local cultural values in Subang Regency - Habiburrahman Daniah; Dede Kosasih; Yatun Romdonah Awaliah (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
Gantangan is a tradition that exists in celebration activities in Subang Regency. This tradition has grown and developed in the local community. In addition, this tradition teaches people to interact socially which has a deep meaning. This study aims to determine the practice, role and cultural values of the gantangan tradition in the Subang Regency community. The method used is a qualitative method with a phenomenological approach. Data were collected by direct observation in the field, interviews, documentation, and literature study. The results of this study are as follows: (1) the gantangan tradition originated from the activities of men when spreading invitations to celebrations using a pack of cigarettes and invited guests donated using a sum of money, then the activity changed to an activity carried out by women using soap as an invitation tool and rice as a means of donation; (2) the gantangan tradition indirectly supports the survival of the community's economy and cultural arts in Subang Regency; (3) the gantangan tradition was born from the community's concern for individuals who will hold a celebration event, besides that the activity also contains cultural values such as the nature of life, the nature of human work, the nature of space and time, the nature with nature, and the nature of fellow humans which can be used as guidance by the community in improving the quality of life.